Polyols - What do we know about their impact on the gut microbiome? - Magda Wojtuś; Sebastian Tomaszuk; Karolina Wąsik (Kazimierz Wielki University, 2022)
Introduction and purpose:  Even though sweeteners' popularity is increasing as they are approved by the Food and Drug Administration (FDA) and generally considered to be safe, their whole impact on the human body is still confusing. Polyols are among one of the most used sweeteners, therefore in this review we will focus on their impact on the gut microbiome as this community of various bacteria influences many aspects of overall health.  Brief description of the state of knowledge:  The current conclusions mostly present prebiotic benefits of polyols and their ability to increase the number of Bifidobacteria, there is research supporting the evidence of it conducted on isomalt, maltitol, lactitol and xylitol. It is possible, as most of them are able to reach the colon. We also investigate other ways sweeteners are shaping the gut microbiome such as multiplication of short chain fatty acids (SCFAs) or decreasing the numbers of Clostridium difficile.  Conclusions:  The impact of polyols on the gut microbiome has many knowledge gaps. More long-term studies are needed in order to consider the individual diversity of the participants' gut microbiota. In order to conduct more valuable conclusions dietary and lifestyle habits should be taken into consideration. All things considered, there is not enough data to clearly determine polyols' role in modifying the gut microbiota.